Cultivation-Independent and Cultivation-Dependent Analysis of Microbes in the Shallow-Sea Hydrothermal System Off Kueishantao Island, Taiwan: Unmasking Heterotrophic Bacterial Diversity and Functional Capacity - Tang, Kai; Zhang, Yao; Lin, Dan; Han, Yu; Chen, Chen-Tung A.; Wang, Deli; Lin, Yu-Shih; Sun, Jia; Zheng, Qiang; Jiao, Nianzhi (Frontiers in Microbiology, 2018)
Shallow-sea hydrothermal systems experience continuous fluctuations of physicochemical conditions due to seawater influx which generates variable habitats, affecting the phylogenetic composition and metabolic potential of microbial communities. Until recently, studies of submarine hydrothermal communities have focused primarily on chemolithoautotrophic organisms, however, there have been limited studies on heterotrophic bacteria. Here, fluorescence in situ hybridization, high throughput 16S rRNA gene amplicon sequencing, and functional metagenomes were used to assess microbial communities from the shallow-sea hydrothermal system off Kueishantao Island, Taiwan. The results showed that the shallow-sea hydrothermal system harbored not only autotrophic bacteria but abundant heterotrophic bacteria. The potential for marker genes sulfur oxidation and carbon fixation were detected in the metagenome datasets, suggesting a role for sulfur and carbon cycling in the shallow-sea hydrothermal system. Furthermore, the presence of diverse genes that encode transporters, glycoside hydrolases, and peptidase indicates the genetic potential for heterotrophic utilization of organic substrates. A total of 408 cultivable heterotrophic bacteria were isolated, in which the taxonomic families typically associated with oligotrophy, copiotrophy, and phototrophy were frequently found. The cultivation-independent and -dependent analyses performed herein show that Alphaproteobacteria and Gammaproteobacteria represent the dominant heterotrophs in the investigated shallow-sea hydrothermal system. Genomic and physiological characterization of a novel strain P5 obtained in this study, belonging to the genus Rhodovulum within Alphaproteobacteria, provides an example of heterotrophic bacteria with major functional capacity presented in the metagenome datasets. Collectively, in addition to autotrophic bacteria, the shallow-sea hydrothermal system also harbors many heterotrophic bacteria with versatile genetic potential to adapt to the unique environmental conditions. □